Phenomenology and ontology in the thought of Edmund Husserl - MIȘCOL, Andrei-Bogdan (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
In this paper I examine Husserlian phenomenology and its relations with a possible ontology that the great German philosopher cultivated as a project, an undeclared ontology. Husserl's expression of the “ultimately and truly absolute” as a “primeval source” is not explained by a declared ontology and the concept of the “continuum” is in the same situation. Claiming that the roots of all ontologies seem to belong in phenomenology, Husserl appears to proclaim the uselessness of developing any ontology. The analysis of the possible development of the Husserlian concepts of “absolute” and “continuum” shows that it would have led Husserl either to an ontology or to the overcoming and dismantling of the phenomenology, because the Husserlian phenomenology and the ontology are actually incompatible. Perhaps that is exactly what he wanted to avoid. The guiding thread of the text is that Husserlian phenomenology is not fully realized as an authentic philosophy without a declared ontology or a clear statement about the relations between phenomenology and ontology.